Acute pulmonary embolism with coexisting right heart thrombi in transit—surgical treatment of 20 consecutive patients. (20th January 2023) - Zieliński, Dariusz; Zygier, Marcin; Dyk, Wojciech; Wojdyga, Ryszard; Wróbel, Krzysztof; Pirsztuk, Ewelina; Szostakiewicz, Katarzyna; Szatkowski, Piotr; Darocha, Szymon; Kurzyna, Marcin; Ciurzyński, Michał; Machowski, Michał; et al.
Abstract: OBJECTIVES: The presence of right heart thrombi in transit (RHTiT) in the setting of acute pulmonary embolism (PE) is associated with high mortality. The optimal management in such cases is inconclusive. We present the results of surgical treatment of 20 consecutive patients diagnosed with high- or intermediate-high-risk PE with coexisting RHTiT. METHODS: A retrospective analysis was performed of all consecutive patients undergoing surgical treatment in the Medicover Hospital between 2013 and 2021 for acute PE with coexisting thrombi in-transit in right heart cavities. The diagnosis was based on echocardiography, computed tomography pulmonary angiography and laboratory tests. Eligibility criteria for surgical treatment were acute PE with RHTiT, right ventricular overload on imaging studies and significantly elevated levels of cardiac troponin and NTproBNP. All patients were operated on with extracorporeal circulation using deep hypothermia and total circulatory arrest. The primary end point was hospital all-cause mortality; secondary end points were perioperative complications and long-term mortality. RESULTS: The analysis included 20 patients. There was no in-hospital death. Nearly one-third of patients required temporal hemofiltration for postoperative renal failure, but this did not involve the need for dialysis at discharge. No neurological complications occurred in any patient. The mean follow-up was 46 months (range 13–98). There was 1 death in the long-term follow-up, not related to PE. CONCLUSIONS: Surgical treatment of patients with acute PE and coexisting RHTiT can provide favourable results. Abstract : Acute pulmonary embolism (PE) occurs with a frequency of 39–115/100 000 and is the third most frequent cause of death among cardiovascular diseases [1].